Homologs of PROTEIN TARGETING TO STARCH Control Starch Granule Initiation in Arabidopsis Leaves. Issue 7 (6th July 2017) - Seung, David; Boudet, Julien; Monroe, Jonathan; Schreier, Tina B.; David, Laure C.; Abt, Melanie; Lu, Kuan-Jen; Zanella, Martina; Zeeman, Samuel C.
Abstract : Two plastidial coiled coil-containing proteins play a critical role in delivering suitable maltooligosaccharide primers to STARCH SYNTHASE4 during starch granule initiation. Abstract: The molecular mechanism that initiates the synthesis of starch granules is poorly understood. Here, we discovered two plastidial proteins involved in granule initiation in Arabidopsis thaliana leaves. Both contain coiled coils and a family-48 carbohydrate binding module (CBM48) and are homologs of the PROTEIN TARGETING TO STARCH (PTST) protein; thus, we named them PTST2 and PTST3. Chloroplasts in mesophyll cells typically contain five to seven granules, but remarkably, most chloroplasts in ptst2 mutants contained zero or one large granule. Chloroplasts in ptst3 had a slight reduction in granule number compared with the wild type, while those of the ptst2 ptst3 double mutant contained even fewer granules than ptst2 . The ptst2 granules were larger but similar in morphology to wild-type granules, but those of the double mutant had an aberrant morphology. Immunoprecipitation showed that PTST2 interacts with STARCH SYNTHASE4 (SS4), which influences granule initiation and morphology. Overexpression of PTST2 resulted in chloroplasts containing many small granules, an effect that was dependent on the presence of SS4. Furthermore, isothermal titration calorimetry revealed that the CBM48 domain of PTST2, which is essential for its function, interacts with long maltooligosaccharides. We propose that PTST2 and PTST3 are critical during granule initiation, as they bind and deliver suitable maltooligosaccharide primers to SS4.